2018
DOI: 10.1007/s00268-018-4524-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Approach for Formal Right and Left Hepatectomy: A Propensity Score Matching Analysis

Abstract: Laparoscopic major hepatectomies are safe and feasible procedures allowing a similar complication rate with a shorter hospital stay and diminished postoperative pain with respect to the standard approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
3
15
3
3
Order By: Relevance
“…MILR is frequently associated with a longer operative time (32,33). However, we did not nd any signi cant difference in operative time for patients undergoing MIRH.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…MILR is frequently associated with a longer operative time (32,33). However, we did not nd any signi cant difference in operative time for patients undergoing MIRH.…”
Section: Discussioncontrasting
confidence: 72%
“…Only recently observational studies with high methodological quality have been published comparing open and minimally invasive major resections (32,33). Takahara et al (34) using PSM showed advantages in terms of blood loss, LoS, and complications with the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies were addressed to study the results of minimally invasive major hepatectomies [ 10 , 26 , 33 ]. Only recently observational studies with high methodological quality have been published comparing open and minimally invasive major resections [ 34 , 35 ]. Takahara et al [ 36 ] using PSM showed advantages in terms of blood loss, length of hospital stay, and complications with the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…MILR is frequently associated with a longer operative time [ 34 , 35 ]. However, we did not find any significant difference in operative time for patients undergoing MIRH.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery has become a standard procedure instead of open approach for many surgical interventions and it is widely used in health services around the world. This rising interest in laparoscopy is based on several benefits, such as better surgical outcomes for patients and resource optimization for healthcare services [1]. Furthermore, this surgical technique has constantly evolved over the past few years, mainly due to training efforts of surgeons [2][3][4] and technological advances of surgical equipment [5].…”
Section: Introductionmentioning
confidence: 99%